2020
DOI: 10.1080/10409289.2020.1848301
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Teachers’ Emotional Exhaustion in Relation to Classroom Instruction and Teacher-child Interactions

Abstract: The present investigation examined the links between preschool teachers' self-reported emotional exhaustion (n = 117) with the quality of their classroom interactions and the dosage and rigor of their instruction. Research Findings: Although teachers' experience of emotional exhaustion was not associated with the dosage and rigor of instruction, more emotionally exhausted teachers demonstrated lower quality interactions with children in their classroom. Additionally, there was some evidence to suggest that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 51 publications
1
40
0
Order By: Relevance
“…Overall, these observational data converge with prior studies of teacher well-being and children’s social and emotional development. Teaching is highly stressful (Johnson et al, 2005) and emotion exhaustion is prevalent within the early childhood workforce (Ansari et al, 2020). When teachers experience stress (either due to their home-lives or their work experiences), the EMOTERS captures both overt negative expressions and the absence of positive expressions in modeling.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these observational data converge with prior studies of teacher well-being and children’s social and emotional development. Teaching is highly stressful (Johnson et al, 2005) and emotion exhaustion is prevalent within the early childhood workforce (Ansari et al, 2020). When teachers experience stress (either due to their home-lives or their work experiences), the EMOTERS captures both overt negative expressions and the absence of positive expressions in modeling.…”
Section: Discussionmentioning
confidence: 99%
“…Lee, Y. H argued that psychological resilience is negatively correlated with emotional failure, and emotional failure is positively correlated with turnover intention [11]. Ansari, A found that the interaction between teachers and students in class and the teaching effect are lower when teachers have more emotional exhaustion [12]. Platsidou, M thought that emotional exhaustion can be predicted by satisfaction with the job and major subscales [13].…”
Section: Hypothesis Proposalmentioning
confidence: 99%
“…However, the teacher is also part of the relationship and what the teacher needs to be able to support the student should not be overlooked. It is not always evident to build close teacher-student relationships with each and every student in your class, and how teachers cope with negative emotions and conflicts in interactions with students is crucial to preserve and maintain teacher sensitivity (Koenen et al, 2019a;Ansari et al, 2020b). For example, if a teacher wants to calm down or console the student following a conflict, they need to be able to cope with their own emotions.…”
Section: Teachers' Relationship-building Competencementioning
confidence: 99%
“…Students who have a close relationship with their teacher for instance hold more positive attitudes toward school, achieve better in class, and are more likely to develop positive peer relations (Roorda et al, 2017(Roorda et al, , 2020Ansari et al, 2020a), while students who have a conflictual relationship with their teacher are at risk for negative outcomes and the amplification of initial internalizing and externalizing problems (Roorda et al, 2014;Ansari et al, 2020a;Nguyen et al, 2020;Roorda and Koomen, 2021). Likewise, close teacher-student relationships contribute to teachers' self-efficacy, sense of personal accomplishment, job satisfaction, and professional motivation (Hagenauer et al, 2015;Corbin et al, 2019;Evans et al, 2019;Aboagye et al, 2020), whereas conflictual relationships are an important source of teacher stress and are predictive of burnout symptoms such as emotional exhaustion (Milatz et al, 2015;Corbin et al, 2019;Ansari et al, 2020b). In sum, both teachers and students profit from close relationships, while both suffer from conflictual relationships.…”
Section: Introductionmentioning
confidence: 99%